1994
DOI: 10.1016/0014-5793(94)80458-3
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase‐C mediates dual modulation of L‐type Ca2+ channels in human vascular smooth muscle

Abstract: The role of protein kinase C @'KC) in cellular regulation of L-type Car' channels was investigated in human umbilical vein smooth muscle. Activation of PKC, by low concentrations (< 30 nM) of 12-O-tetradecanoyl-phorbol-13-acetate (TPA) caused inhibition of Ca*' channels, while higher concentrations of TPA (>lOO nM) elicited a transient rise, followed by sustained inhibition of Ca*' channel activity in cell-attached patches. Low TPA concentrations predominantly reduced channel availability, while high concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
1

Year Published

1995
1995
2000
2000

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 19 publications
4
34
1
Order By: Relevance
“…Tautomycin markedly inhibited mean Ca 2÷ channel activity in human vascular smooth muscle. This finding is in accordance with the concept of smooth muscle L-type Ca 2+ channels being subject to phosphorylation-dependent down-regulation [4][5][6][7]. Inhibitory phoshorylation of smooth muscle Ca 2+ channels has been suggested to involve cyclic nucleotide-dependent protein kinases [6] and/or specific isoforms of protein kinase C [7].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Tautomycin markedly inhibited mean Ca 2÷ channel activity in human vascular smooth muscle. This finding is in accordance with the concept of smooth muscle L-type Ca 2+ channels being subject to phosphorylation-dependent down-regulation [4][5][6][7]. Inhibitory phoshorylation of smooth muscle Ca 2+ channels has been suggested to involve cyclic nucleotide-dependent protein kinases [6] and/or specific isoforms of protein kinase C [7].…”
Section: Discussionsupporting
confidence: 89%
“…the channels' availability. We have recently reported on a dual regulation of human smooth muscle Ca 2+ channels by activation of protein kinase C [7], and demonstrated that protein kinase C-mediated inhibition is associated with reduced channel availability. Similarly the inhibitory effect of tautomycin was found to be based predominantly on a reduction of channel availability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, PKC has been reported to uncouple G-proteins from opioid receptors in guinea-pig striatal membranes and SH-SY5Y cells (Lin et al, 1994). Furthermore, PKC is known to modulate the activity of various ion channels (Shearman et al, 1989;Petersen & Berridge, 1994;Tuominen et al, 1994), including the L-type VSCC (Schuhmann & Groschner, 1994). As activation of PLC stimulates PKC activity, via diacylglycerol, in addition to stimulating Ins(1,4,5)P3 formation (Berridge, 1993), p-opioids would also be expected to increase PKC activity in SH-SY5Y cells.…”
Section: Introducdonmentioning
confidence: 99%